Perlindungan Hak Perempuan dan Anak dalam Perkara Perceraian di Pengadilan Agama - Keshia Monika Prianto; Mega Dewi Ambarwati (JURNAL ILMIAH NUSANTARA, 2025)
Divorce often has significant impacts on the lives of women and children. This study aims to analyze the legal protections available for women's and children's rights in divorce cases in Indonesia. Through literature review and case analysis, this research identifies various forms of legal protection established by laws and regulations. However, practical challenges remain in providing optimal protection. The study concludes that comprehensive efforts are needed to enhance public legal awareness, strengthen law enforcement, and provide adequate support services for women and children affected by divorce.